2009
DOI: 10.1016/j.ibmb.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The Anopheles gambiae adult midgut peritrophic matrix proteome

Abstract: Malaria is a devastating disease. For transmission to occur, Plasmodium, the causative agent of malaria, must complete a complex developmental cycle in its mosquito vector. Thus, the mosquito is a potential target for disease control. Plasmodium ookinetes, which develop within the mosquito midgut, must first cross the midgut's peritrophic matrix (PM), a thick extracellular sheath that completely surrounds the blood meal. The PM poses a partial, natural barrier against parasite invasion of the midgut and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
108
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 50 publications
7
108
1
2
Order By: Relevance
“…This varying degree of thickness of PM could be due to differential peritrophin expression observed. In the present study, it was observed that most of the peritrophin genes were upregulated by 24 h following blood meal which corroborates with maximum thickness of peritrophic matrix observed at the same time 19 . Earlier, Dana et al 23 demonstrated that the midgut transcripts including peritrophins were present as early as 30 min post-blood meal and further categorized the timedependent differential expression of peritrophins in A. gambiae into early-, mid-and late-phase genes.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…This varying degree of thickness of PM could be due to differential peritrophin expression observed. In the present study, it was observed that most of the peritrophin genes were upregulated by 24 h following blood meal which corroborates with maximum thickness of peritrophic matrix observed at the same time 19 . Earlier, Dana et al 23 demonstrated that the midgut transcripts including peritrophins were present as early as 30 min post-blood meal and further categorized the timedependent differential expression of peritrophins in A. gambiae into early-, mid-and late-phase genes.…”
supporting
confidence: 88%
“…Temporal regulation of secretory vesicular appearance process where PM precursors are accumulated was also demonstrated in the midgut of A. darlingi 25 , A. albimanus 13 and A. stephensi 26 . In contrast, in A. aegypti, the vesicles are formed de novo after blood feeding 19 . The early-, mid-and late-stage peritrophin expression in the A. stephensi midgut observed in our study corroborates with previous studies.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Using RNA sequencing, the authors first determined gene expression in midgut cells at 48 and 72 h after feeding mature adults on trypanosome-infected or normal blood. Aksoy et al found that trypanosomes reduced the expression of peritrophins, structural proteins that bind chitin, and digestive enzymes, both associated with PM formation in insects (16)(17)(18). Then Aksoy et al (14) used the entomopathogenic Serratia marcescens in an elegant microbial assay to assess the PM integrity in tsetse flies.…”
mentioning
confidence: 99%